Glyphosate effect on Merremia aegyptia water transpiration and water use efficiency - M Negrisoli, Raphael [UNESP] (2023)
Water availability is a concern for agricultural production and sustainability, escalating the need for an efficient weed control. Weeds are in direct competition with crops for water and its unsuccessful control risks water management across the crop season. However, little is known regarding the impact of herbicide on weed water use behavior. Thus, the objective of this study was to unveil the effect of glyphosate doses on Merremia aegyptia (L.) Urb. water transpiration, water use efficiency (WUE), and intrinsic water use efficiency (iWUE). Two greenhouse studies were conducted using the troublesome weed hairy woodrose (M. aegyptia) in four glyphosate doses (1.4; 15; 111; and 740 g a.e. ha−1) plus an untreated control. Water transpiration was measured in a 3-day-interval until 21 days after treatment (DAT), determining WUE based on its dry biomass and water use. iWUE was determined at 21 DAT through IRGA analysis. Glyphosate label dose (740 g a.e. ha−1) effectively reduced water transpiration 3 DAT and ceased whole water transpiration by 12 DAT. Lower doses (111 and 15 g a.e. ha−1) reduced 39 and 20% of water transpiration, in comparison to the untreated control, and increased its iWUE. Therefore, label dose application of glyphosate successfully controlled hairy woodrose and ceased its water transpiration.